Kinetic insights into the peroxygenase activity of cellulose-active lytic polysaccharide monooxygenases (LPMOs) - Riin Kont (Nature Portfolio, 2020)
Lytic polysaccharide monooxygenases (LPMOs) catalyze the hydroxylation of glycosidic bonds in polysaccharides, but the catalytic properties of these monocopper enzymes remain poorly characterized. Here authors employ competition between reference enzymes and LPMOs for the H2O2 co-substrate to kinetically characterize LPMO-catalyzed cellulose oxidation.